Does Everyone Have a Gender? Compulsory Gender, Gender Detachment, and Asexuality - Canton Winer (Socius)
Feminist scholars have written for decades about the radical potential, if not the necessity, of ungendering for resisting gender inequality. Yet much of this work has been theoretical, and other scholars have questioned whether ungendering is even possible. Drawing on interviews with 30 asexual individuals, the author presents empirical findings that lend support to the plausibility of ungendering. On the basis of these findings, the author introduces the concept of gender detachment , which refers to individually held notions that gender is irrelevant, unimportant, pointless, and/or overall not a helpful framework for understanding and defining the self. The author argues that the difficulty of navigating these feelings highlights gender, and not merely the gender binary, as a compulsory system of categorization. The author also argues that this finding highlights the need to theorize around compulsory gender . The author concludes by discussing gender detachment’s connections to and differences from the concepts of degendering, ungendering, undoing gender, redoing gender, nonbinary identification, and gender vertigo. The author also considers gender detachment’s potential for radical resistance to gender (and the inequality gender produces) and the potential complications in realizing that potential.